CMOS class AB second generation voltage conveyor - Kumngern, Montree; Torteanchai, Usa; Khateb, Fabian (My University, 2019)
This paper presents a class AB second generation voltage conveyor. This device is designed to obtain the current buffer as input stage and is followed by the voltage buffer in monolithic chip. A class AB technique to obtaining high signal swing, high dynamic range, high bandwidth and low power consumption has been used. The proposed circuit is simulated using SPICE simulations with a standard 0.18 μ m CMOS process and with ± 0.9V supply.
Keywords: analog circuit; class AB circuit; second generation voltage conveyor; voltage conveyor